Sirt1 rescues the obesity induced by insulin‐resistant constitutively‐nuclear FoxO1 in POMC neurons of male mice. (14th July 2014) - Susanti, Vina Yanti; Sasaki, Tsutomu; Yokota‐Hashimoto, Hiromi; Matsui, Sho; Lee, Yong‐Soo; Kikuchi, Osamu; Shimpuku, Mayumi; Kim, Hye‐Jin; Kobayashi, Masaki; Kitamura, Tadahiro
<x xml:space="preserve">Abstract</x> Objective The hypothalamus is the brain center that controls the energy balance. Anorexigenic proopiomelanocortin (POMC) neurons and orexigenic AgRP neurons in the arcuate nucleus of the hypothalamus plays critical roles in energy balance regulation. FoxO1 is a transcription factor regulated by insulin signaling that is deacetylated by Sirt1, a nicotinamide adenine dinucleotide‐ (NAD+‐) dependent deacetylase. Overexpression of insulin‐resistant constitutively‐nuclear FoxO1 (CN‐FoxO1) in POMC neurons leads to obesity, whereas Sirt1 overexpression in POMC neurons leads to leanness. Whether overexpression of Sirt1 in POMC neurons could rescue the obesity caused by insulin‐resistant CN‐FoxO1 was tested here. Methods POMC neuron‐specific CN‐FoxO1/Sirt1 double‐KI (DKI) mice were analyzed. Results The obese phenotype of CN‐FoxO1 KI mice was rescued in male DKI mice. Reduced O2 consumption, increased adiposity, and fewer POMC neurons observed in CN‐FoxO1 mice were rescued in male DKI mice without affecting food intake and locomotor activity. Sirt1 overexpression decreased FoxO1 acetylation and protein levels without affecting its nuclear localization in mouse embryonic fibroblasts and hypothalamic N41 cells. Conclusions Sirt1 rescues the obesity induced by insulin‐resistant CN‐FoxO1 in POMC neurons of male mice by decreasing FoxO1 protein through deacetylation. Sirt1 ameliorates obesity caused by a genetic model of central insulin resistance.